Study of Drug Utilization Pattern for Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Patients Attending a Government Hospital in Kerala, India - Veettil, Sajesh Kalkandi (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: Drug utilization studies are powerful exploratory tools to ascertain the role of drugs in society. This study was conducted to establish the drug utilization pattern and the common adverse drug reactions for the treatment of acute exacerbation of chronic obstructive pulmonary disease (COPD) in one of the government hospitals in Kerala, India. METHODS: This was a prospective observational study aimed at recognizing the drug utilization pattern for the treatment of acute exacerbation of COPD for 7-day under nonexperimental settings. All information significant to the study was collected from the case records and discussions conducted with the inpatients and bystanders during ward rounds, with the support of a physician. Moreover, daily follow-ups were conducted to assemble data on amendment in therapy, add-on therapy, and clinical improvement until the patient was discharged from the hospital or to an upper limit of 7-day, whichever is earlier. RESULTS: All the patients in this study received combination therapy. Among the inhalational β-agonists, salbutamol accounted for 74% use. Parenteral steroids were used in 78% of the patients and all of them received hydrocortisone. Steroid inhalers were used only in 25% of the patients. Anticholinergics were used in 77.5% of patients. Antibiotics were used in 86.7% patients. The main adverse effects noted were dry mouth (15%) and bad taste (10%) and these adverse effects were highly correlated with the use of anticholinergics (P < 0.05). CONCLUSIONS: Despite the use of drugs according to the availability and physician's preference, it was found in the analysis that majority were in accordance with Global Initiative for Chronic Obstructive Lung Disease criteria recommendations.